2020
DOI: 10.1017/s0022050720000315
|View full text |Cite
|
Sign up to set email alerts
|

Transportation and Health in the Antebellum United States, 1820–1847

Abstract: I study the impact of transportation on health in the rural United States, 1820–1847. Measuring health by average stature, I find that greater transportation linkage, as measured by market access, in a cohort’s county-year of birth had an adverse impact on its health. A one-standard-deviation increase in market access reduced average stature by 0.14 inches, and rising market access over the study period can explain 37 percent of the contemporaneous decline in average stature, known as the Antebellum Puzzle. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…We also show that our results are robust to exploiting variation at the state level in Online Appendix D. 42 The value of the instrument for each municipality is presented in The controls most crucial to our identification are, following Sequeira, Nunn, and Qian (2020), the number of years that a municipality was connected to the railway network by 1920 and an indicator variable for municipalities that were not connected by 1920. 43 These controls address the obvious concern that rail linkage may have had direct effects on economic activity (Summerhill 2005), and that the location of rail construction was not random, likely targeting areas where economic activity was or would be greater (e.g., Atack et al 2010;Donaldson and Hornbeck 2016;Zimran 2020).…”
Section: Empirical Strategymentioning
confidence: 99%
“…We also show that our results are robust to exploiting variation at the state level in Online Appendix D. 42 The value of the instrument for each municipality is presented in The controls most crucial to our identification are, following Sequeira, Nunn, and Qian (2020), the number of years that a municipality was connected to the railway network by 1920 and an indicator variable for municipalities that were not connected by 1920. 43 These controls address the obvious concern that rail linkage may have had direct effects on economic activity (Summerhill 2005), and that the location of rail construction was not random, likely targeting areas where economic activity was or would be greater (e.g., Atack et al 2010;Donaldson and Hornbeck 2016;Zimran 2020).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Basic transport network expansion, such as railways, roads, and canals, is seen as a means to increase market access, reduce transaction costs, and provide more incentives for productivity improvements and market-oriented economic activities. In previous research, transport network expansion is found to be significantly linked to historical improvements in agricultural activities (Atack and Margo 2011;Donaldson 2018;Donaldson and Hornbeck 2016), market integration (Brunt and Cannon 2014;Jacks 2005), economic specialization (Niemi 1970), industrial development and productivity (Bogart and Chaudhary 2013;Tang 2014), urbanization (Rae 1944;Berger and Enflo 2017), changes in trade patterns (Fletcher 1958), income levels (Banerjee, Duflo, and Qian 2020), and even detriments to health (Zimran 2020). Although previous studies shed light on the aggregate spillover effects of transport network development within an agent's locality, there is little discussion to what extent the aggregate effect is driven by those agents located directly adjacent to transport infrastructure.…”
mentioning
confidence: 92%
“…3 A notable exception is Atack, Margo, and Perlman (2012), who study U.S. school attendance in the nineteenth century. Tang (2017), similarly, looks at mortality effects of railroads in Meiji Japan, while Zimran (2020) examines impacts on stature in the United States. Our paper looks at the effects of historical railroads on literacy and enrollment, outcomes more commonly examined in work on recent transportation projects (roads and highways) rather than older projects (railroads).…”
mentioning
confidence: 99%